Antioxidant Capacity of Selected Plant Extracts and Their Essential Oils - Charalampos Proestos; Konstantina Lytoudi; Olga Konstantina Mavromelanidou; Panagiotis Zoumpoulakis; Vassileia J. Sinanoglou (MDPI AG, 2013)
The main objective of this study was the screening of some selected aromatic plants very popular in Greece, with respect to their total phenolic content, antioxidant capacity, reducing activity, and oxidative stability. All plants were extracted with the conventional method, reflux with methanol. The essential oils of the plants were also analyzed for their antioxidant properties. The total phenolic content was determined by the Folin-Ciocalteu method using gallic acid as the standard, while the phenolic substances were identified and quantified by High Performance Liquid Chromatography (HPLC) coupled with a multi-wavelength ultraviolet-visible (UV-vis) detector. The antioxidant capacity of the plant extracts was measured by their ability to scavenge free radicals such as (a) DPPH (2,2-diphenyl-1-picrylhydrazyl) and, (b) ABTS (2,2'-azinobis-(3-ethylbenzothiaziline-6- sulfonate). The Folin-Ciocalteu method proved the existence of antioxidants in the aromatic plant extracts. Taking into account the results of the DPPH and ABTS methods, the free radical scavenging capacity was confirmed. Eventually, all plants exhibited low but noticeable protection levels against lipid oxidation, as determined by the Rancimat test.